2022
DOI: 10.3390/socsci11030117
|View full text |Cite
|
Sign up to set email alerts
|

Disaster Resilience Differs between Survivors and Victims’ Families: A Semantic Network Analysis

Abstract: The main purpose of this study is to clarify the difference in disaster resilience between survivors and victims’ families by analyzing the language used in popular literature on disaster cases. The results showed that there were differences in emotions, behaviors, attitudes, role perceptions, etc., between survivors and victims’ families in dealing with a disaster. In particular, survivors remember and think about the situation that occurred at the time of the disaster, which creates resilience to the inciden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 71 publications
0
1
0
Order By: Relevance
“…The far-reaching aftermath of accidents like the Sewol disaster is profoundly distressing. A survey revealed that 41.4 % of victims considered suicide, 67 % of victims quit their jobs, and 73 % faced severe disruptions in their social relations (Lee et al, 2022;Yen et al, 2018).…”
Section: Social Dimensionmentioning
confidence: 99%
“…The far-reaching aftermath of accidents like the Sewol disaster is profoundly distressing. A survey revealed that 41.4 % of victims considered suicide, 67 % of victims quit their jobs, and 73 % faced severe disruptions in their social relations (Lee et al, 2022;Yen et al, 2018).…”
Section: Social Dimensionmentioning
confidence: 99%